KESIAPSIAGAAN DAN MANAJEMEN PENGETAHUAN KELUARGA DALAM MENGHADAPI BENCANA LAHAR KALI PUTIH DI DESA SIRAHAN KECAMATAN SALAM KABUPATEN MAGELANG - , DIAN INDIRA WAHYUNITA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Kali Putih is one of lahar flow path in Magelang Regency which has high potential of hazard. The biggest lahar flow in kali Putih occurred in January 2011, and Sirahan is one of village wich severely affected. Not only knowledge of the community affected by lahar is important to learn, but also preparedness become important factor involved in disaster management effort. The aim of this research is to measure family preparedness and knowledge management deal with lahar in Sirahan Village. Family preparedness was analyzed using descriptive statistics. Furthermore, knowledge management was analyzed using qualitative methods with interactive models. Family preparedness data was collected by using the questionnaire, and knowledge management data was collected by interviewing responden. The result of family preparedness are family who was affected by lahar more prepared than family who was not affected. The result of knowledge management showed that (1) Electronic media, incidental sosialitation, and simulation are based resource information in family knowledge, (2) There are different distribution of knowledge before and after lahar in January 2011, (3) Eksplisit form of the utilization knowledge management output are family preparedness appeals. Early warning system and mobilization need to get more attention as efforts to improve familiy preparedness. In addition, optimalitation of the role of other family members also need to be considered.